KARAKTERISTIK PERMEN JELLY SARI KULIT BUAH NAGA (Hylocsreus polyhizus) DENGAN VARIASI PENAMBAHAN BUBUK JAHE (Zingiber rose): Characteristics of Dragon Fruit Skin (Hylocsreus Polyhizus) Jelly Candy with Additional Variations of Ginger Powder (Zingiber Rose) - Anggatio Prasetio , Bagus Setyawan, Arfiati Ulfa Utami (Program Studi Teknologi Hasil Pertanian Universitas PGRI Banyuwangi, 2022)
Red dragon fruit peel contains pectin and anthocyanins which can be used as alternative natural ingredients for food products. In addition, Indonesia is famous for its abundant spices, one of which is ginger which has a distinctive taste and flovor caused,ginger contains antimicrobial substances. One of the product innovations utilizing dragon fruit peel is the manufacture of jelly candy with the addition of. Does this study aim to determine: (a) How is the effect of adding ginger powder on the chemical characteristics of dragon fruit peel jelly candy (b) To find out which comparative treatment of using ginger powder on dragon fruit peel jelly candy is the best and which is preferred by consumer. This study is an experimental study using RAL consisting of 6 treatments with 4 replications, namely the concentration of red dragon fruit peel extract 250g with variations of ginger powder P1 2g, P2 3g, P3 4g, P4 5g, and P5 6g then analyzed using One Way Anova) with chemical test parameters and organoleptic tests analyzed descriptively. The results obtained from this study were on the moisture content the best treatment was P1 with a value of 16%. The best pH test results are P1 with a pH value of 6,26. The results of the organoleptic test showed that the texture test parameters at P2 with the addition of 3g ginger powder, aroma test at P1 with the addition of 2g, taste test parameters at P5 with the addition of 6g and color test parameters at P3 with the addition of 4g ginger powder